Meme Sebagai Representasi Kritik dan kebebasan Berpendapat di Ruang Siber - Prapti Wigati Purwaningrum (Wanastra: Jurnal Bahasa dan Sastra, 2020)
Abstrak  - The purposes of this study is to describe what and how memes in social media Instagram as the representation of critics from netizen. The approach of this study is Critical Discourse Analysis by Fairclough with three dimensions; text, discursive practice, and social practice. The writer chooses meme in @fakartun Instagram account as the data source because meme full of funny picture and simple text, easy to understand, and lead the reader to think twice to find the implied meaning in it. This research is focused on meme in @fakartun Instagram account, especially pictures, text, and caption. The conclusion of this study is the writer found social media as a space for netizen to get  and upload many information widely and effectively. Nowadays memes are no longer just pictures and funny words that are entertaining but become a media to express opinions, criticize a policy or an event that is happening. Finally, the findings of this analysis will describe how the patterns of opinion, commenting, and critical thinking of citizens in cyberspace Keywords: Critical Discourse Analysis, Fairclough, memes, Instagram, @fakartun